One Health come utopia della scienza e scienza dell'utopia . evidenze da uno studio di caso sul benessere animale, umano e ambientale negli allevamenti di bovine da latte - Balduzzi, Giacomo; Favretto, Anna Rosa (Cambio (Firenze), 2021)
The One Health approach emphasises the need to tackle the challenges of human, animal and ecosystem health using a more integrated approach. Since the mid-2000s and even more since the outbreak of the Covid-19 pandemic, public health scholars and policy makers have been paying an increasing attention to the One Health approach. The authors retrace the different reconstructions on the origins and meanings of the One Health approach with the use of an interdisciplinary case study jointly conducted by sociologists and veterinary epidemiologists in the context of dairy cattle farms located in the provinces of Turin and Cuneo. In the context of the "risk society" theorised by Ulrich Beck, the division of labour between science, politics and economics breaks apart and has to be renegotiated. In such a perspective, One Health appears as a utopia of science structured as a field of research and interdisciplinary intervention held together by a common project of the future. Besides, One Health is a science of utopia aimed at avoiding the disaster with the same tools that scientists use to foresee the possibility of it happening in the future.